Detection Of Crimean-Congo Hemorrhagic Fever Seroprevalence Rate In Occupational Persons In Nineveh Province, Iraq (Tikrit Journal of Veterinary Science, 2024)
Crimean–Congo hemorrhagic fever  (CCHF) one of zoonotic viral tick born disease can infect both animals and human. Occupational persons which they are in direct contact with animals were at high risk . The disease infect animals by silent form and  humans by severe type. Butchers 120 samples and veterinarians 83 samples  were two occupational person groups sera targeted in our study. Results showed positive seroprevalence rate for the sera of butchers (9/120) 7.5 % , veterinarians (6/83) 7.228 % to CCHF by ELISA test.  The highest results recorded according to age : butchers (2/19)  10.526 % with ages